PERAN KEPEMIMPINAN ISLAMI DALAM PENINGKATAN MANAJEMEN USAHA PERUSAHAAN - Maratun Shalihah (TAHKIM, 2017)
Islamic Leadership, a leadership model that has transcendental values, which rests on the Quran and Sunnah. But in its development, the application of the current Islamic leadership looks increasingly short of expectations. According to Islam leadership is trust. Because the leaders of the company must have four characters, the honest (shidiq), trust (trustworthy), fathanah (smart) and Tabliq (transparent, open). In practice, the leadership must be based on the principle: monotheism, deliberation, fairness and freedom. The results of the application of Islamic leadership within the company, are the results in order to meet the necessities of life, for the benefit of families and businesses to work as good deeds. Keywords: Islamic leadership, management, company